2021
DOI: 10.1002/cbic.202100265
|View full text |Cite
|
Sign up to set email alerts
|

Remote Photodamaging of DNA by Photoinduced Energy Transport

Abstract: Local DNA photodamaging by light is well-studied and leads to a number of structurally identified direct damage, in particular cyclobutane pyrimidine dimers, and indirect oxidatively generated damage, such as 8-oxo-7,8-hydroxyguanine. Similar damages have now been found at remote sites, at least more than 105 Å (30 base pairs) away from the site of photoexcitation. In contrast to the established mechanisms of local DNA photodamaging, the processes of remote photodamage are only partially understood. Known path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 118 publications
0
19
0
1
Order By: Relevance
“…Furthermore, it is our hope that our results could benchmark the future calculations that aim to reveal the key vibrational mode that accounts for the ultrafast ISC in dCyd. The elucidation of the ISC mechanism in dCyd is important because a long-lived triplet excited state could lead to the formation of deleterious photoproducts in both DNA and RNA. Therefore, this study also paves the path to further study dCyd triplet state-involved photophysical and photochemical properties in DNA and RNA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it is our hope that our results could benchmark the future calculations that aim to reveal the key vibrational mode that accounts for the ultrafast ISC in dCyd. The elucidation of the ISC mechanism in dCyd is important because a long-lived triplet excited state could lead to the formation of deleterious photoproducts in both DNA and RNA. Therefore, this study also paves the path to further study dCyd triplet state-involved photophysical and photochemical properties in DNA and RNA.…”
Section: Discussionmentioning
confidence: 93%
“…Ultraviolet (UV) radiation-initialized photochemical reactions are one of the greatest threats to the biological genome on Earth since all canonical nucleobases, which are building blocks of DNA/RNA, absorb strongly in the UVC region (<280 nm). Fortunately, these DNA bases can dissipate over 90% of their excited-state energy through efficient non-radiative channels to the ground state, which guarantees the intrinsic photostability of nucleic acid. However, increasing evidence has shown that photophysics and photochemistry in DNA and RNA are also associated with longer-lived excited states such as lower-lying dark nπ* states and triplet excited states. In particular, triplet excited states are of special interest as they can lead to photolesions such as cyclobutene pyrimidine dimers (CPDs), pyrimidine (6–4) pyrimidone photoproducts, one-electron oxidation, H-abstraction, and intrabase cross-link in DNA and RNA. Therefore, it is essential to understand triplet state-involved excited-state dynamics in DNA/RNA as it can provide the chemical reaction mechanism for the above-mentioned photolesions.…”
Section: Introductionmentioning
confidence: 99%
“…Relative chemiluminescence was calculated with respect to the control experiment containing ONOO − with no substrate, defined as 1.0 (raw data in Figures S1−S5 singlet oxygen. 22 Therefore, they are not expected to emit chemiluminescence. The signal for all compounds (except the flavins) was 2-to 7-fold above background, with melatonin oxidation producing the highest luminescence emission intensity (Figures 2a and S1−S4).…”
Section: Chemiexcitation Creates Triplet States In Indolamine and Cat...mentioning
confidence: 99%
“…Moreover, how far the energy migrates in DNA to eventually produce photodamage is still a matter of concern. 35 , 36 …”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, Cbz can be excited selectively in the presence of Thy, and also, Cbz exhibits a moderate intersystem crossing quantum yield (0.36), a relatively high triplet energy (70.2 kcal mol –1 ), a ππ* triplet configuration (free from the problems associated with the competitive hydrogen abstraction by benzophenone), and a reasonably long-living triplet excited state. Moreover, how far the energy migrates in DNA to eventually produce photodamage is still a matter of concern. , …”
Section: Introductionmentioning
confidence: 99%